2017
DOI: 10.1002/jcla.22261
|View full text |Cite
|
Sign up to set email alerts
|

M2BPGi as a potential diagnostic tool of cirrhosis in Chinese patients with Hepatitis B virus infection

Abstract: M2BPGi levels increased with the progression of liver fibrosis in HBV infected patients. M2BPGi can be served as a potential glycobiomarker to assess the stage of liver fibrosis, especially for the diagnosis of cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…M2BPGi levels in patients with chronic hepatitis B increase as liver fibrosis progresses. The mean M2BPGi COI values in histological fibrosis stages 1, 2, 3, and 4 are 0.26-0.9, 0.34-1.36, 0.57-1.65, and 1.21-3.1, respectively (Table 1) [52][53][54][55][56][57][58]. M2B-PGi was significantly lower in patients with chronic hepatitis B than in those with chronic hepatitis C [59].…”
Section: Utility Of M2bpgi In Chronic Hepatitis Bmentioning
confidence: 94%
“…M2BPGi levels in patients with chronic hepatitis B increase as liver fibrosis progresses. The mean M2BPGi COI values in histological fibrosis stages 1, 2, 3, and 4 are 0.26-0.9, 0.34-1.36, 0.57-1.65, and 1.21-3.1, respectively (Table 1) [52][53][54][55][56][57][58]. M2B-PGi was significantly lower in patients with chronic hepatitis B than in those with chronic hepatitis C [59].…”
Section: Utility Of M2bpgi In Chronic Hepatitis Bmentioning
confidence: 94%
“…Zou et al 26 reported WFA+-M2BP was useful to assess early stages of liver fibrosis, and Ura et al 36 showed WFA+-M2BP was more accurate in diagnosing significant fibrosis than advanced fibrosis. In contrast, several other studies indicated that WFA+-M2BP had the strongest ability to predict cirrhosis 37,62 . In our metaanalysis, we found that the overall AUSROCs of WFA+-M2BP for identifying mild fibrosis, significant fibrosis, advanced fibrosis and cirrhosis were 0.75, 0.79, 0.82 and 0.88, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…WFA+-M2BP is a serum glycobiomarker that is receiving growing attentions. It had been reported that the elevated WFA+-M2BP level was associated with the risk of HCC [57][58][59] , the loss of HBeAg in chronic hepatitis B patients 60 , and the severity of liver fibrosis 61,62 . In our meta-analysis, we evaluated 36 articles in total, and explored the predictive accuracy of WFA+-M2BP for distinguishing liver fibrosis stages and HCC by comparing with diverse non-invasive indicators.…”
Section: Discussionmentioning
confidence: 99%
“…M2BPGi has also been found to be useful in the assessment of fibrosis in other liver diseases. Wei et al [23] observed a positive correlation of M2BPGi with the progression of fibrosis in patients with chronic hepatitis B.…”
Section: Discussionmentioning
confidence: 98%